A Bacterial Symbiont Protects Honey Bees from Fungal Disease - Delaney L. Miller (American Society for Microbiology, 2021)
Fungi can play critical roles in host microbiomes (5–7), yet bacterial-fungal interactions are understudied. For insects, fungi are the leading cause of disease (5, 8).